2021
DOI: 10.1038/s41598-021-98798-9
|View full text |Cite
|
Sign up to set email alerts
|

Adults with Crohn’s disease exhibit elevated gynoid fat and reduced android fat irrespective of disease relapse or remission

Abstract: Crohn’s disease (CD) is a debilitating inflammatory bowel condition of unknown aetiology that is growing in prevalence globally. Large-scale studies have determined associations between female obesity or low body mass index (BMI) with risk of CD at all ages or 8– < 40 years, respectively. For males, low BMI entering adult life is associated with increased incidence of CD or ulcerative colitis up to 40 years later. Body composition analysis has shown that combinations of lean tissue loss and high visceral fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…However, strenuous activity and total daily physical activity were positively associated with complete mucosal healing within the last 6 months. Similar results were found in a small cohort study of CD patients [14]. The physical activity level measured with actigraphy was not different between remising and relapsing patients.…”
Section: Potential Benefits Of Physical Activity In Inflammatory Bowe...supporting
confidence: 89%
“…However, strenuous activity and total daily physical activity were positively associated with complete mucosal healing within the last 6 months. Similar results were found in a small cohort study of CD patients [14]. The physical activity level measured with actigraphy was not different between remising and relapsing patients.…”
Section: Potential Benefits Of Physical Activity In Inflammatory Bowe...supporting
confidence: 89%
“…Crohn's disease is a representative chronic inflammatory disease. In contrast to the conclusions of most studies, 18,19 Dowling et al 20 found that adult patients with Crohn's disease exhibited less fat in the android region and more fat in the gynoid region compared with the healthy population, independent of changes in disease. The mesenteric adipose tissue encapsulating the diseased intestine, also known as "creeping fat," is a protective barrier against inflammatory mediators and intestinal bacterial translocation, 21 and its presence is limited to the android region.…”
Section: Discussionmentioning
confidence: 77%
“… 7 Furthermore, a recent study showed the male patients of the participating CD had significantly higher BMI compared to the general healthy Irish population, while lean tissue mass was similar. 8 In addition, the majority of body fat was located in the abdominal or trunk region, 8 such as mesenteric creeping fat. All the above studies indicate that BMI cannot account for fat distribution without distinction between lean and fat mass.…”
Section: Introductionmentioning
confidence: 99%